Pediatric Trauma Mortality in Jerusalem’s Israeli Healthcare System: A Retrospective Analysis - Rebecca Brooks; Daniel Marcus; Hagay Stern; David Rekhtman; Saar Hashavya; Shaden Salameh; Giora Weiser; Uri Pollak; Jacques Braun; Itai Shavit (Journal of Epidemiology and Global Health)
Abstract Jerusalem's intricate geopolitical environment, ethnic diversity, and divided healthcare systems between its East and West regions may impact pediatric trauma mortality. This study investigated pediatric trauma mortality rates in Jerusalem's Israeli healthcare system. We conducted a retrospective cohort study on Jerusalem residents under 18 who died from trauma in the Emergency Department (ED) or within a week of hospital admission (ED/7-day) between January 2013, and December 2023. Jerusalem's overall population data were obtained from the Israel Central Bureau of Statistics. During the study period, 121 pediatric trauma patients had ED/7-day death, 82 were Jerusalem residents. The annual mortality incidence among the city population was 2.1/100,000. Twenty-three children were Jews and 59 were East Jerusalem Arabs. The trauma mortality Incidence Rate Ratio for Arab versus Jewish children was 3.6 (95% CI 2.2–5.9). Death was declared upon ED arrival or within one hour in 52% (95% CI 30.6–73.1%) and 64% (95% CI 50.9–76.4%) of the Jewish and Arab children, respectively. In 2/23 [8.7% (95% CI 1.0–28.0%)] Jews, and 2/59 [3.4% (95% CI 0.4–11.7%)] Arabs, death occurred due to an injury related to the Israeli-Palestinian conflict. In 13/59 [22% (95% CI 12.3–34.7%)] of the Arabs, resuscitation was initiated in a community clinic before the arrival of Emergency Medical Services (EMS), and in 5/59 [8.5% (95% CI 2.8–18.7%)] the child was brought to the hospital by caregivers rather than by EMS. This study provides evidence that Jerusalem’s child trauma death rate in Jerusalem’s Israeli healthcare system is comparable to high-income European countries. However, East Jerusalem Arab children are more vulnerable to trauma-related deaths than Jewish children. These results provide a basis for targeted trauma prevention programs.